Pharmacokinetic incompatibility of the Huanglian-Gancao herb pair - Ji-Quan Zhang; Rui Wang; Ting Zhou; Qing Zhao; Chun-Cao Zhao; Bing-Liang Ma (BMC, 2020)
Abstract Background Pharmacokinetic interaction is one of the most important indices for the evaluation of the compatibility of herbal medicines. Both Gancao (Glycyrrhizae Radix et Rhizoma) and Huanglian (Coptidis Rhizoma) are commonly used traditional Chinese medicines (TCMs). In this study, the influence of Gancao on the pharmacokinetics of Huanglian was systematically studied by using berberine as a pharmacokinetic marker. Methods Extracts of the herbal pieces of Huanglian and the herb pair (Huanglian plus Gancao) were prepared with boiling water. The concentration of berberine in the samples was analyzed using liquid chromatography-mass spectrometry. The total amounts of berberine in all extract samples were compared. Comparative pharmacokinetic studies of Huanglian and the herb pair were conducted in ICR mice. In vitro berberine absorption and efflux were studied using mice gut sacs. The equilibrium solubility of berberine in the extracts was determined. The in vitro dissolution of berberine was comparatively studied using a rotating basket method. Results Gancao significantly reduced berberine exposure in the portal circulation (425.8 ng·h/mL vs. 270.4 ng·h/mL) and the liver (29,500.8 ng·h/mL vs. 15,422.4 ng·h/mL) of the mice. In addition, Gancao decreased the peak concentration (Cmax) of berberine in the portal circulation (104.3 ng·h/mL vs. 76.5 ng·h/mL) and liver (4926.1 ng·h/mL vs. 2642.8 ng·h/mL) of mice. Significant influences of Gancao on the amount of berberine extracted (32% reduction), the solubility of berberine (34.7% compared with the control group), and dissolution (88.7% vs. 66.1% at 15 min in acid buffer and 68% vs. 51.8% at 15 min in phosphate buffer) were also revealed. Comparative pharmacokinetic studies in ICR mice indicated that the formation of sediment was unfavorable in terms of berberine absorption (345.3 ng·h/mL vs. 119.8 ng·h/mL). Conclusions Gancao was able to reduce intestinal absorption and in vivo exposure of berberine in Huanglian via the formation of sediment, which caused reductions in the extracted amount, solubility, and dissolution of berberine.